2010
DOI: 10.1007/s12192-009-0146-5
|View full text |Cite
|
Sign up to set email alerts
|

Circulating heat shock protein 70 (HSPA1A) in normal and pathological pregnancies

Abstract: Heat shock proteins (Hsps) are ubiquitous and phylogenetically conserved molecules. They are usually considered to be intracellular proteins with molecular chaperone and cytoprotective functions. However, Hsp70 (HSPA1A) is present in the peripheral circulation of healthy nonpregnant and pregnant individuals. In normal pregnancy, circulating Hsp70 levels are decreased, and show a positive correlation with gestational age and an inverse correlation with maternal age. The capacity of extracellular Hsp70 to elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 142 publications
(121 reference statements)
3
70
0
Order By: Relevance
“…When HSPs are released into the extracellular compartment, they are able to deliver a partial maturation signal to dendritic cells, which may play a crucial role in pathogenesis of asthma and activate the NF-kappaB pathway, and can also stimulate pro-inflammatory cytokines production in vitro (Asea et al 2000;Basu et al 2000). This suggests that HSP70 may modulate and exert immune and inflammatory responses and may be involved in the pathogenesis and/or be markers of some diseases like atherosclerosis, ischemia-reperfusion injury, preeclampsia, and HELLP syndrome (Bielecka-Dabrowa et al 2009;Molvarec et al 2007Molvarec et al , 2009Molvarec et al , 2010Walsh et al 2009). Meanwhile, it has been found that extracellular HSP70 level is increased in patients with sarcoidosis and chronic beryllium disease (Silva et al 2007) and COPD patients (Hacker et al 2009).…”
mentioning
confidence: 99%
“…When HSPs are released into the extracellular compartment, they are able to deliver a partial maturation signal to dendritic cells, which may play a crucial role in pathogenesis of asthma and activate the NF-kappaB pathway, and can also stimulate pro-inflammatory cytokines production in vitro (Asea et al 2000;Basu et al 2000). This suggests that HSP70 may modulate and exert immune and inflammatory responses and may be involved in the pathogenesis and/or be markers of some diseases like atherosclerosis, ischemia-reperfusion injury, preeclampsia, and HELLP syndrome (Bielecka-Dabrowa et al 2009;Molvarec et al 2007Molvarec et al , 2009Molvarec et al , 2010Walsh et al 2009). Meanwhile, it has been found that extracellular HSP70 level is increased in patients with sarcoidosis and chronic beryllium disease (Silva et al 2007) and COPD patients (Hacker et al 2009).…”
mentioning
confidence: 99%
“…Soluble Hsp70 showed no apparent endogenous circadian rhythm in a rested state (Fortes and Whitham 2009). Elevated serum Hsp70 level was measured in pathologic pregnancies (Molvarec et al 2009) such as preeclampsia and hemolytic anemia elevated liver enzymes low platelet count syndrome. Increased serum levels of Hsp70 levels were reported in patients with peripheral and renal vascular disease (Wright et al 2000) and after acute myocardial infarction (Dybdahl et al 2005;Satoh et al 2006), whereas circulating Hsp70 levels were positively related to markers of tissue damage including creatine kinase MB and cardiac troponin T. In chronic heart failure (CHF) patients increased serum Hsp70 levels were found compared to healthy controls (Genth-Zotz et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated HSP70 was demonstrated in the HELLP syndrome, and HSP70 levels were associated with an increased risk of several pregnancy Table 2 a Spearman's rank-order correlation coefficients (r) with p values are presented complications (Molvarec et al 2010). Furthermore, increased HSP70 levels were found in patients with advanced, chronic heart failure, and were correlated with the markers of heart function (Gombos et al 2008).…”
Section: Discussionmentioning
confidence: 99%